Valuation of Second Pillar Pension Products in Slovakia - Špirková, Jana; Kollár, Igor; Szűcs, Gábor; Spišiaková, Mária (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This paper presents selected products of the payout phase of the second pillar pension scheme in the Slovak Republic which are stated by Act 43/2004 Coll. on the Old-Age Pension Saving Scheme and on amendments to some acts. By means of stochastic modeling of the force of mortality, it models and analyses the amounts of pension annuities in the selected designed products of the second pillar pension saving according to the requirements of the Council Directive 2004/113/EC, which sets the rules on gender-neutral pricing in insurance, and of the Council Directive 2009/138/EC, which, among other things, sets also the rules relating to the technical provisions, Solvency Capital Requirement, Minimum Capital Requirement and investment rules
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 441-452
Keywords: annuity; product; force of mortality; technical interest rate; gender